Hazards and Disasters and Industrial Disaster Risk and Management in Jaipur Municipal Region: A Study on Industrial Disaster Risk and Management in Jaipur Municipal Region (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Human society, the natural environment, and disasters have been intertwined since the startof civilization. These catastrophes result in significant human and environmental losses, and they pose asevere danger to the environment. Three million people have been murdered, a billion people have beeninjured, and billions of dollars in material damage has been caused by natural disasters in the last twentyyears. Although risk assessment may be performed at any point in the life cycle of an industrial system,it is most useful and fruitful when performed at the outset of the development of the industrial project,new technology, equipment, process, procedure, etc. If we want to stop incidents from happening, weneed to investigate them thoroughly. The accurate knowledge of accident kinds and causes, distributionthroughout the year, and what may be averted is gained by accident analysis.